The Use of Tenecteplase in Combination with Brain Scan Analysis in Thrombolysis of Acute Ischemic Stroke: A Moroccan Experience - Haddouali, Kamal; El Bidaoui, Zahra; Ait Lahcen, Karima; Khattab, Hajar; Bellakhdar, Salma; Chikhaoui, Nabil; El Otmani, Hicham; Moutawakil, Bouchra El; RAFAI, MOHAMMED ABDOH (International Journal of Innovative Research in Medical Science, 2024)
Objective: Intravenous thrombolysis of acute ischemic stroke uses alteplase, which has long been approved for this indication. In the same context, studies on Tenecteplase have demonstrated the efficacy and safety of this molecule, which we use in our structure following clinical and radiological evaluation using non-enhanced computed tomography. Our aim is to share our institutional approach. Materials and Methods: Retrospective, descriptive, cross-sectional study in the neurology department of Casablanca over a 5-year period from 01 January 2018 to 31 December 2022. We included all patients with suspected acute stroke who underwent IVT with Tenecteplase with an Alberta Stroke Program Early CT Score greater than or equal to 7 on non-enhanced cerebral computed tomography. The Modified Rankin Scale was evaluated at 3 months. Results: During these 5 years, 140 patients (49% were females) had received Tenecteplase thrombolytic therapy. The mean age was 67 years, mean National Institutes of Health Stroke Scale was 13/42, mean Alberta Stroke Program Early CT Score was 8/10. 97% of the patients received a dose of 0.25mg/kg of Tenecteplase in a mean time of 210min from the onset of symptoms. The Modified Rankin Scale between 0 and 2 at 3 months was in 46% and 13% of death. Conclusion: We are satisfied with the results of Intravenous thrombolysis with Tenecteplase. However, we are convinced of the limited information provided by a non-enhanced cerebral computed tomography to brain magnetic resonance imaging which remains difficult to access in our context.